Quantitative and carbon isotope ratio analysis of fatty acids isolated from human brain hemispheres. Issue 1 (2nd November 2022) - Lacombe, R. J. Scott; Smith, Mackenzie E.; Perlman, Kelly; Turecki, Gustavo; Mechawar, Naguib; Bazinet, Richard P.
Abstract: Our knowledge surrounding the overall fatty acid profile of the adult human brain has been largely limited to extrapolations from brain regions in which the distribution of fatty acids varies. This is especially problematic when modeling brain fatty acid metabolism, therefore, an updated estimate of whole‐brain fatty acid concentration is necessitated. Here, we sought to conduct a comprehensive quantitative analysis of fatty acids from entire well‐characterized human brain hemispheres ( n = 6) provided by the Douglas‐Bell Canada Brain Bank. Additionally, exploratory natural abundance carbon isotope ratio (CIR; δ 13 C, 13 C/ 12 C) analysis was performed to assess the origin of brain fatty acids. Brain fatty acid methyl esters (FAMEs) were quantified by gas chromatography (GC)‐flame ionization detection and minor n‐6 and n‐3 polyunsaturated fatty acid pentafluorobenzyl esters by GC‐mass spectrometry. Carbon isotope ratio values of identifiable FAMEs were measured by GC‐combustion‐isotope ratio mass spectrometry. Overall, the most abundant fatty acid in the human brain was oleic acid, followed by stearic acid (STA), palmitic acid (PAM), docosahexaenoic acid (DHA), and arachidonic acid (ARA). Interestingly, cholesterol as well as saturates including PAM and STA were most enriched in 13 C, while PUFAs including DHA and ARA were most depleted in 13 C. These findings suggest a contribution of endogenous synthesis utilizing dietary sugar substrates rich in 13 C, and a combination of marine, animal, and terrestrial PUFA sources more depleted in 13 C, respectively. These results provide novel insights on cerebral fatty acid origin and concentration, the latter serving as a valuable resource for future modeling of fatty acid metabolism in the human brain. Abstract : We quantified fatty acids (FAs) from whole human brain hemispheres as previous estimates were limited to extrapolations from brain regions in which the distribution of FAs varies. The most abundant FAs were oleic, stearic, palmitic (PAM), docosahexaenoic (DHA), and arachidonic (ARA) acid. Exploratory carbon isotope ratios (CIRs; 13 C/ 12 C) of PAM and downstream FAs suggest a contribution of endogenous synthesis from sugars rich in 13 C, while DHA and ARA CIRs reflect a combination of marine, animal and terrestrial polyunsaturated FA sources deplete in 13 C. Results serve as a resource for modeling brain FA metabolism and provide insight into brain FA origin.